Trend Of Graduates Of Agricultural Disciplines and their Impact on the received Status of Business Organizations (A survey study of the Opinions of a Samples of traders with the Directorate of Agriculture in Najaf Governorate ) - Ameen, Saleem M.; Ameer, Arshad A.; Alsayyed, Abdulnaser A. (Journal of Kerbala for Agricultural Sciences, 2018)
The trend is Consider one of the terms that the researchers depend upon it in their studies specially in the field of psychology, because it has a clear effect on changing activity and of individual to that activity. As the activity of agricultural field is Considered from vital tributaries which the government has to pay attention to them, especially as many countries of the world are flourishing and growing in this filed, they need to do a lot of work to Support this vital sector, through supporting the academic institutions to train the future skills, to maintains this activity to go with development and environmental changes, within this sector. In addition to that, the government should work to find business organization that provide facilities and support to this sector such as agriculture directorate specialized agricultural bank to provide its requirements. It is worth mention if those organizations want to remain a competitive work environment and grow in a dynamic and so histicuted environment and a complex communication network, the must meet the needs of their customers and obtain their satisfaction either it is a service or a commodity provided to them to occupy these organization their perceived status. So, the importance of this study has emerged through the effect of the components of trend of agricultural graduates disciplines to show the perceived states of business organizations in particular at level of country in general by identifying those components as well as identifying the dimensions of perceived status in line with trends of individuals. The study concludes that the knowledge ranked first by trend Component influences on the highlight of perceived states of studied organization by its behavioral dimension which linked first among its dimensions from the point of view of the sample.